1974
DOI: 10.1111/j.1365-2621.1974.tb01748.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and gelation of modified potato starches

Abstract: The gelation characteristics of natural potato starch and two modified starches have been compared with their water sorption isotherms determined at 25°C. The pregelatinized starch gels more readily than the natural starch, but has a lower water sorption capacity below 90% relative humidity.The cross-linked starch gels less readily than the natural starch on heating but has a similar water sorption isotherm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This could be due to the low damaged starch content of cassava flour, which allows strong bonds to be formed between starch granules and water molecules (Satin, 1988). The method of dough preparation possibly accounts for this, the bonds within the starch granules having been denatured to a reasonable extent (Chilton & Collison, 1974). Comparatively, the specific heat values obtained for wheat-maize composite bread dough were lower than that for 100% wheat bread dough.…”
Section: Thermal Propertiesmentioning
confidence: 91%
“…This could be due to the low damaged starch content of cassava flour, which allows strong bonds to be formed between starch granules and water molecules (Satin, 1988). The method of dough preparation possibly accounts for this, the bonds within the starch granules having been denatured to a reasonable extent (Chilton & Collison, 1974). Comparatively, the specific heat values obtained for wheat-maize composite bread dough were lower than that for 100% wheat bread dough.…”
Section: Thermal Propertiesmentioning
confidence: 91%
“…The flow behaviour and textural characteristics of cross‐linked starches are very complex due to the effects of starch concentration, heating rate, heating temperature and the amount of shear, as well as competition with other dissolved solutes and polymers 19–21. Cross‐linking at low levels, although having a substantial effect on properties such as granule swelling, paste viscosity, and retrogradation,12, 15, 22 contributes little to water sorption properties 23. The objective of the present study was to compare the effect of EPI and POCl 3 on the physico‐chemical, thermal, rheological and retrogradation properties of starches from different potato cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…The general increase in both water and oil absorption capacities of maize flour with an increase in the steaming duration may be attributed to the seeming severe disruption in the structural make-up of the starch in the flour occasioned by the steaming operation. It had earlier been observed that the increase in the water absorption capacity of pregelatinized flour might be due to such factors as higher degree of damaged starch in the flour (Chilton and Collison 1974;Kurimoto and Shelton 1988;Adeyemi et al 1989) while the increase in oil absorption capacity was attributed to degree of denatured protein constituent in the flour, temperature of treatment and particle size of the flour (Richest et al 1974). The damaged starch content in maize flour obtained from steamed maize grits is also presented in Table 1.…”
Section: Resultsmentioning
confidence: 97%